The concept of internet of things and its challenges to privacy - Mohamed, Sidi Mohamed Ould; Zulhuda, Sonny (2015)
People today live in a connected environment that can negatively or positively affect almost all aspects of life. The Internet of Things (IoT) is a term used to describe the ubiquitous smart devices that can connect to the Internet. The IoT was described by advocates as “the first real evolution of the Internet” that can improve the way people live-in terms of education, work, healthcare, entertainment and so forth. However, the IoT has a cost especially when it comes to security and privacy. It also raises serious questions which need to be legally addressed. For example, how these smart devices generated, stored and collected information? Who own that information? And who will be responsible in case of damage? This paper attempts to discuss the concept of the IoT from various aspects including its pros and cons- in order to clarify the term as it is used by the experts and researchers. In addition to that, the paper also goes further to touch upon the IoT challenges to privacy from legal perspective. Last but not least, the paper provides recommendations on how to protect privacy and reap IoT’s advantages. Furthermore, it is argued that a study such this will positively contribute to the academic discussion as it looks at IoT from one of its most contentious aspects (privacy challenges) that could slow IoT progress.